Nontuberculous Mycobacteria - Tan, Shera; Kasperbauer, Shannon (Seminars in Respiratory and Critical Care Medicine, 2021)
Nontuberculous mycobacteria (NTM) are ubiquitous in the environment and 193 species of NTM have been discovered thus far. NTM species vary in virulence from benign environmental organisms to difficult-to-treat human pathogens. Pulmonary infections remain the most common manifestation of NTM disease in humans and bronchiectasis continues to be a major risk factor for NTM pulmonary disease (NTM PD). This article will provide a useful introduction and framework for clinicians involved in the management of bronchiectasis and NTM. It includes an overview of the epidemiology, pathogenesis, diagnosis, and management of NTM PD. We will address the challenges faced in the diagnosis of NTM PD and the importance of subspeciation in guiding treatment and follow-up, especially in Mycobacterium abscessus infections. The treatment of both Mycobacterium avium complex and M. abscessus, the two most common NTM species known to cause disease, will be discussed in detail. Elements of the recent ATS/ERS/ESCMID/IDSA NTM guidelines published in 2020 will also be reviewed.
Keywords: nontuberculous mycobacteria; bronchiectasis; Mycobacterium avium complex; Mycobacterium abscessus; diagnosis; treatment